Collective Myopia in Japanese Organizations A Transcultural Approach for Identifying Corporate Meltdowns - Chikudate, Nobuyuki; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Drawing on European philosophies, this book examines collective myopia and its role in global business through various case studies of Japanese organizations, including the Tokyo Electric Power Company.
Keywords: Business; Leadership; Organization; Planning; International business enterprises; Behavioral economics; International economics; Business and Management; International Business; Organization; International Economics; Business Strategy/Leadership.; Behavioral/Experimental Economics; Electronic books